Bibliometric Analysis of Household Physics in Scopus Database: Approaches with Bibliometrix R-package and VOSviewer (Review of Literature on Home Physics Education) - Fatra Faiza Majid; Buyamin Buyamin (Universitas Lambung Mangkurat, 2024)
This study conducts bibliometric research using the Bibliometrix R-package analysis and VOSviewer to analyse Scopus databases from 1921 to 2024, specifically focusing on physics and households. It aims to determine the number of writings on home physics education in scientific publications, analyse publication trends, identify prolific authors, identify frequently used keywords and subject areas, and identify the countries that make the most contributions to publication. The research study found one article and was the only one published in 1921, entitled